The Effect of Long Storage of Whole Blood Components on the Level of 2,3 Diphosphoglycerate and Lactic Acid in the Blood Bank, Dr. Soetomo General Hospital, Surabaya, Indonesia - Dwi Ajeng Roosanti; Betty Agustina Tambunan; Arifoel Hajat (Institute of Medico-legal Publications Pvt Ltd, 2022)
The purpose of this study was to analyze changes in levels of 2,3 DPG and lactic acid on WB storagetime. This research is an observational analytical with time series design was conducted at the ClinicalPathology Installation and Blood Bank Dr. Soetomo General Hospital Surabaya in the period July- September 2020. Levels of 2,3 DPG and lactic acid were measured in 16 bags of Whole Bloodcomponents on the day 1, day 5, day 10, day 20 and day 30. Statistical analysis was performed usingthe Friedman test. The results were statistically significant if p <0.05. The Friedman statistical testshowed that there were significant differences in levels of 2.3 DPG (p <0.001) and levels of lacticacid (p <0.001) during storage. The results showed that the level of 2,3 DPG in WB which was storeddecreased according to the duration of storage. The yield of lactic acid on stored WB increased withthe duration of storage. Therefore, saving WB is recommended to be given within <6 days to reducethe risk of acidosis. Further research is needed for other parameters that can affect the storage process.